Impact of suppressing retinoic acid‐related orphan receptor gamma t (ROR)γt in ameliorating central nervous system autoimmunity. (January 2015) - Yang, Y.; Winger, R. C.; Lee, P. W.; Nuro‐Gyina, P. K.; Minc, A.; Larson, M.; Liu, Y.; Pei, W.; Rieser, E.; Racke, M. K.; Lovett‐Racke, A. E.
Summary Multiple sclerosis (MS) is an immune‐mediated chronic central nervous system (CNS) disease affecting more than 400 000 people in the United States. Myelin‐reactive CD4 T cells play critical roles in the formation of acute inflammatory lesions and disease progression in MS and experimental autoimmune encephalomyelitis (EAE), a well‐defined mouse model for MS. Current MS therapies are only partially effective, making it necessary to develop more effective therapies that specifically target pathogenic myelin‐specific CD4 T cells for MS treatment. While suppressing T‐bet, the key transcription factor in T helper type 1 (Th1) cells, has been demonstrated to be beneficial in prevention and treatment of EAE, the therapeutic potential of retinoic acid‐related orphan receptor gamma t (ROR)γt, the key transcription factor for Th17 cells, has not been well‐characterized. In this study, we characterized the correlation between RORγt expression and other factors affecting T cell encephalitogenicity and evaluated the therapeutic potential of targeting RORγt by siRNA inhibition of RORγt. Our data showed that RORγt expression correlates with interleukin (IL)‐17 production, but not with the encephalitogenicity of myelin‐specific CD4 T cells. IL‐23, a cytokine that enhances encephalitogenicity, does not enhance RORγt expression significantly. Additionally, granulocyte–macrophage colony‐stimulating factor (GM‐CSF) levels, which correlate with the encephalitogenicity of different myelin‐specific CD4 T cell populations, do not correlate with RORγt. More importantly, inhibiting RORγt expression in myelin‐specific CD4 T cells with an siRNA does not reduce disease severity significantly in adoptively transferred EAE. Thus, RORγt is unlikely to be a more effective therapeutic target for ameliorating pathogenicity of encephalitogenic CD4 T cells.